2022
DOI: 10.1002/1873-3468.14366
|View full text |Cite
|
Sign up to set email alerts
|

The activator/repressor Hap1 binds to the yeast eIF5A‐encoding gene TIF51A to adapt its expression to the mitochondrial functional status

Abstract: Mitochondrial activity adapts to cellular energetic and metabolic demands; its dysfunction is a hallmark of ageing and many human diseases. The evolutionarily conserved translation elongation factor eIF5A is involved in maintaining mitochondrial function. In humans, eIF5A is encoded by two highly homologous but differentially expressed genes; in yeast, these are TIF51A and TIF51B. We show that yeast transcription factor Hap1 constitutively binds to the TIF51A promoter to activate its expression under respirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…We and others have found that eIF5A is necessary to maintain high mitochondrial activity; additionally, several mitoproteins whose levels drop in the absence of functional eIF5A have been identified in yeast and mammalian cells (26,27,35,36). In order to expand our knowledge on the role of eIF5A in mitochondria, we performed a proteomic experiment in which a wild-type and two eIF5A temperaturesensitive mutant yeast strains, tif51A-1 carrying a single point mutation (Pro83 to Ser) and tif51A-3 carrying a double point mutation (Cys39 to Tyr, Gly118 to Asp) (37,38), were exponentially grown in YPD media at 25°C and then incubated at 41°C for 4 h to deplete eIF5A.…”
Section: Depletion Of Eif5a Results In the Down-regulation Of Many Mi...mentioning
confidence: 95%
See 1 more Smart Citation
“…We and others have found that eIF5A is necessary to maintain high mitochondrial activity; additionally, several mitoproteins whose levels drop in the absence of functional eIF5A have been identified in yeast and mammalian cells (26,27,35,36). In order to expand our knowledge on the role of eIF5A in mitochondria, we performed a proteomic experiment in which a wild-type and two eIF5A temperaturesensitive mutant yeast strains, tif51A-1 carrying a single point mutation (Pro83 to Ser) and tif51A-3 carrying a double point mutation (Cys39 to Tyr, Gly118 to Asp) (37,38), were exponentially grown in YPD media at 25°C and then incubated at 41°C for 4 h to deplete eIF5A.…”
Section: Depletion Of Eif5a Results In the Down-regulation Of Many Mi...mentioning
confidence: 95%
“…eIF5A expression is regulated according to the metabolic demands of the cell. In yeast, TIF51A gene is up-regulated under respiratory conditions by the transcription (activator/repressor) factor Hap1 (26, 27), which responds to changes in oxygen and heme levels to activate the transcription of many respiratory genes (28). However, under hypoxic/non-respiratory conditions, Hap1 represses TIF51A expression (26, 27).…”
mentioning
confidence: 99%
“…With the exception of ERG7 and ERG2 , these results suggest that Hap1 directly represses ERG gene expression during the initial stages of iron deficiency by recruiting the corepressor Tup1. Recently, it has been shown that iron depletion also induces the Hap1‐Tup1‐mediated repression of the eIF5A encoding gene TIF51A (Barba‐Aliaga & Alepuz, 2022 ). Similar to iron depletion, previous studies have shown that the recruitment to ERG gene promoters of corepressor factors, such as Tup1/Ssn6 and also Set4, increases upon hypoxic conditions in a Hap1‐dependent manner (Hickman & Winston, 2007 ; Serratore et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) assays were performed as previously described (Barba‐Aliaga & Alepuz, 2022 ) in strains expressing myc‐HAP1 or TUP1‐myc allele and also in strains expressing untagged HAP1 or TUP1 as control for background binding. For immunoprecipitation, an anti‐c‐myc antibody (Invitrogen) was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation